2019
DOI: 10.1097/md.0000000000015937
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of acupuncture plus fire needle versus acupuncture alone in lateral epicondylitis

Abstract: Background: The aim of this study was to compare the short-term and intermediate-term efficacy of acupuncture plus fire needle therapy with that of acupuncture alone in the treatment of lateral epicondylitis (LE). Methods: Thirty-eight patients with LE who had persisted for at least 2 months were enrolled in this prospective, assessor-blinded, randomized controlled pilot trial. Twenty-one patients were randomized to the acupuncture plus fire needle group and 17 to the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 22 publications
(23 reference statements)
0
21
0
Order By: Relevance
“…In 1 study [23], the elctroacupuncture treatment showed a statistically significant difference in all items pre and post treatment, and had excellent beneficial effect. In another study [16], burning acupuncture showed no statistically significant differences in the treatment group compared with the control group, so it was reported that there need to be additional research. In 1 study [22], bee venom pharmoacopuncture showed no statistically significant difference in increasing grip strength pre-and post-treatment, but it was perceived by patients to be statistically significantly more effective than acupuncture.…”
Section: Analysis Of Treatment Effectmentioning
confidence: 96%
See 4 more Smart Citations
“…In 1 study [23], the elctroacupuncture treatment showed a statistically significant difference in all items pre and post treatment, and had excellent beneficial effect. In another study [16], burning acupuncture showed no statistically significant differences in the treatment group compared with the control group, so it was reported that there need to be additional research. In 1 study [22], bee venom pharmoacopuncture showed no statistically significant difference in increasing grip strength pre-and post-treatment, but it was perceived by patients to be statistically significantly more effective than acupuncture.…”
Section: Analysis Of Treatment Effectmentioning
confidence: 96%
“…1). There were 9 RCTs [16][17][18][19][20][21][22][23][24] and 18 [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] case reports included in the review. The main characteristics of these studies was presented in tables (Tables 2 and 3).…”
Section: Description Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations